2016
DOI: 10.1016/j.jss.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Revascularization and muscle adaptation to limb demand ischemia in diet-induced obese mice

Abstract: Background Obesity and type 2 diabetes are major risk factors for peripheral arterial disease (PAD) in humans which can result in lower limb demand ischemia and exercise intolerance. Exercise triggers skeletal muscle adaptation including increased vasculogenesis. The goal of this study was to determine whether demand ischemia modulates revascularization, fiber size, and signaling pathways in the ischemic hind limb muscles of mice with diet-induced obesity (DIO). Materials and Methods DIO mice (n=7) underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
0
1
1
Order By: Relevance
“…the advanced stage of LEAD), Lejay et al 37 reported that moderate forced treadmill running for 3 weeks induced increased transcript levels of PGC-1α, PGC-1β and NRF-1 in both non-ischemic and non-ischemic tibialis muscle 37 . In LEAD mice, results are inconsistent with the study from Albadawi et al 24 showing upregulation of ischemic tibialis muscle PGC-1α mRNA level 24 , and the study of Nagase et al 21 , which like ours observed no increase in ischemic soleus muscle PGC-1α mRNA expression 21 after treadmill exercise. Again, none of these animal studies have examined whether mitochondrial content and expression of genes involved in mitochondrial-related biogenesis can be influenced by exercise type, as well as whether such possible adaptations translate into a functional gain in hindlimb use.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…the advanced stage of LEAD), Lejay et al 37 reported that moderate forced treadmill running for 3 weeks induced increased transcript levels of PGC-1α, PGC-1β and NRF-1 in both non-ischemic and non-ischemic tibialis muscle 37 . In LEAD mice, results are inconsistent with the study from Albadawi et al 24 showing upregulation of ischemic tibialis muscle PGC-1α mRNA level 24 , and the study of Nagase et al 21 , which like ours observed no increase in ischemic soleus muscle PGC-1α mRNA expression 21 after treadmill exercise. Again, none of these animal studies have examined whether mitochondrial content and expression of genes involved in mitochondrial-related biogenesis can be influenced by exercise type, as well as whether such possible adaptations translate into a functional gain in hindlimb use.…”
Section: Discussioncontrasting
confidence: 97%
“…Moreover, Willmann et al 23 reported increased ischemic muscle microvessel density and VEGF receptor 2 protein expression after 4 weeks of forced treadmill exercise in C57BL/6 mice with unilateral hindlimb ischemia 23 . Lastly, in mice with diet-induced obesity and unilateral femoral artery ligation, daily forced treadmill running for 4 weeks enhanced capillary density, but mRNA and protein levels of VEGF in the tibialis anterior muscle remained unchanged 24 . While these differences might be attributed, in part, to inter-laboratory differences in methodology and protocol, we have strived in our LEAD mouse study to identify which exercise regimen is effective at improving voluntary exercise capacity, and whether or not underlying mechanisms implicate hemodynamic and/or metabolic adaptations.…”
Section: Discussionmentioning
confidence: 93%
“…In agreement with our data, Kivela et al reported no difference in muscle VEGFA mRNA expression between trained and sedentary mice, but also between three and five times per week exercised mice [38]. In ischemic hindlimb muscle tissues, previous studies from our lab and from Albadawil et al also showed no effect of treadmill running five times/week [13] and seven times/week [17] on VEGFA and/or HIF-1α mRNA expression. Altogether, one could hypothesize that exercise frequency does not modulate VEGFA and/or HIF-1α expression in ischemic and non-ischemic muscles, at least at the transcriptional level.…”
Section: Discussionsupporting
confidence: 92%
“…In line with our study, Nagase et al demonstrated no increase in ischemic muscle PGC-1α gene expression after three weeks of treadmill exercise performed twice a week despite increased endurance performance [15]. In contrast, Albadawil et al showed enhanced PGC-1α mRNA expression in ischemic muscle of mice that underwent 60 min of daily treadmill exercise over 4 weeks [17]. Additional research is to be considered to clarify the role of exercise frequency on mitochondrial biogenesis in skeletal muscle ischemic disorders.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation